Neoplasias oculares primárias malignas confirmadas por histopatologia em duas décadas no município de Passo Fundo no Rio Grande do Sul - Miyano Filho, Sergio Koji (2020)
Objective - To demonstrate the epidemiological, histopathological and clinical profile of primary orbital and ocular cancer in Passo Fundo, Rio Grande do Sul, Brazil. Methods - The study included 70 medical records of patients with malignant orbital and ocular tumors diagnosed between 1998 and 2018, including all histological subtypes found. Data were collected from medical records filed at Hospital São Vicente de Paulo (HSVP) and at the Pathology Institute of Passo Fundo (IPPF). The parameters obtained were sex, age, race, origin, alcoholism, smoking, histopathological diagnosis, topography of the primary tumor, first treatment received at the hospital, state of the disease after the first treatment and basic cause of death. The data are like absolute and relative frequency distribution. Results - Most patients lived outside of Passo Fundo (78.95%), eye orbit cancer had a higher prevalence in males (58.57%), whites were the most affected (92.42%). The percentage of smokers in the sample was higher than in the Brazilian population in general (35.48%), the first treatment received in hospital, in most cases (68.63%) was surgery and in 59,5% of cases there was complete remission of the tumor after initial therapy. The histopathological types found were melanoma and carcinoma (38.57%) and the conjunctiva was affected in 44.28% of the cases. The main intraocular structure affected for the ciliary body with 12.85% of cases, which were also the main cause of registered deaths, with 37.04%. Conclusions - Most of the results of the study converge with the findings of other studies. The predominance of conjunctiva carcinoma, uveal melanoma and conjunctiva melanoma is that a population is exposed to known risk factors. As this was the first survey of orbital neoplasms in the north of Rio Grande do Sul, further studies are treated for better comparison.